2010
DOI: 10.1161/circulationaha.109.933465
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Root Pseudoaneurysm 1 Year After Transapical Aortic Valve Implantation

Abstract: A n 84-year-old woman was admitted to our institution for transapical aortic valve implantation (TAVI) because of severe aortic stenosis coexisting with high-risk clinical conditions. She had a past history of type 2 diabetes mellitus, hypertension, intrinsic asthma, moderate to severe chronic renal insufficiency (Modification of Diet in Renal Disease glomerular filtration rate, 36 mL/min per 1.73 m 2 ), and peripheral atherosclerotic vascular disease involving both iliofemoral arteries. Eighteen months before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…Although the clinical impact of untreated contained rupture is unknown, it appears conceivable that the occurrence of contained rupture as an assumed prestage to uncontained rupture should be avoided. Interestingly, in all 3 cases observed in the present study, as well as in the 2 cases described in literature so far, 13,15 contained rupture occurred adjacent to the left coronary sinus. This leads to the assumption that the tissue adjacent to the left coronary sinus represents a Locus minoris resistentiae.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Although the clinical impact of untreated contained rupture is unknown, it appears conceivable that the occurrence of contained rupture as an assumed prestage to uncontained rupture should be avoided. Interestingly, in all 3 cases observed in the present study, as well as in the 2 cases described in literature so far, 13,15 contained rupture occurred adjacent to the left coronary sinus. This leads to the assumption that the tissue adjacent to the left coronary sinus represents a Locus minoris resistentiae.…”
Section: Discussionsupporting
confidence: 77%
“…8,13,15,24 In theory, both entities may belong to the spectrum of the same pathology, namely disruption of the aortoventricular junction, caused by either the forces of the preceding valvuloplasty or the actual TAVI procedure. In the study presented, we found 3 cases of contained rupture of the aortic root by means of MSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three cases have been published until today with confirmed aortic dissection as a cause of death following TAVI via the transapical and transfemoral route, respectively . In two cases (one transfemoral and one transapical), death occurred several days after the index procedure, whereas the third case was discovered as late as 1 year after transapical aortic valve implantation . In general, the observation of aneurysm formation after TAVI as seen in the present case highlights a new potential cause of unexplained death or clinical detoriation several days to months after TAVI.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, a number of complications have been reported after the introduction of a percutaneous valve holder through the apex of the left ventricle. 9,10 In addition, although feasible, redo sternotomy in patients with patent grafts remains a risky procedure.…”
mentioning
confidence: 99%